MORPHOFUNCTIONAL AND PSYCHOMOTRICAL ASPECTS OF THE PUPILS FROM SECONDARY SCHOOLS - Ioan Sorin Gălățeanu; Petru Ghervan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
We ask ourselves the natural question of the importance of these particularities and the answer is simple to find: the activity of physical education and sport is not carried out at random, but it has a scientific foundation without which it is impossible to achieve the strengthening of health, the harmonious physical development, the acquisition of some motor skills necessary for various activities and the achieving of superior sports results. The research carried out has shown that the student between 11 and 14 years old goes through a phase where growth is dynamic, where there are transformations that will eventually lead to maturity. It is the period when childhood ends and the somato-functional growth processes are accelerated. A first aspect to be noted for this age is that of the differentiated growth regarding boys-girls, a fact that makes the two sexes become differentiated at the end of puberty (10-14 years). According to the results of the specialists in the field, the somatic growth of students highlights the fact that they can cope with moderate efforts in terms of speed, strength and skill, with the mention that boys show greater availability to girls. The oina game, through its characteristics, can solve these problems very well by helping